Structures, antimicrobial activity, DNA interaction and molecular docking studies of sulfamethoxazolyl-azo-acetylacetone and its nickel(II) complex. (15th October 2015) - Das, Dipankar; Sahu, Nilima; Mondal, Sudipa; Roy, Suman; Dutta, Paramita; Gupta, Suvroma; Mondal, Tapan Kumar; Sinha, Chittaranjan
Graphical abstract: Sulfamethoxazolyl-azo-acetylacetone and nickel(II) complex are structurally characterized. They are active against B. subtilis and E. coli . Interaction of CT DNA is stronger with nickel(II) complex than the ligand. Molecular docking approach is used to account the binding of the ligand with DHPS protein of E. coli . The time dependent DFT computation has been used to explain the electronic spectra of the compounds. Abstract: 4-(Z)-((2-Hydroxy-4-oxopent-2-en-3-yl)diazenyl)-N-(5-methylisoxazol-3-yl)benzene sulfonamide (HL) and its nickel(II) complex [Ni(L)2 (H2 O)4 ] have been characterized by spectroscopic and single crystal X-ray diffraction measurements. Time dependent DFT computations have been used to explain the electronic spectra of the compounds. The interaction of CT DNA with [Ni(L)2 (H2 O)4 ] ( K b, 12.20 × 10 5 M −1 ) is stronger than with HL ( K b, 6.09 × 10 5 M −1 ). The antimicrobial activity of HL and the Ni(II) complex has been examined against Bacillus subtilis (ATCC 6633; IC50 : 63.72 μg/ml (HL) and 81.49 μg/ml ([Ni(L)2 (H2 O)4 ])) and Escherichia coli (ATCC 8739; IC50 : 77.25 μg/ml (HL) and 78.28 μg/ml ([Ni(L)2 (H2 O)4 ])). The in-silico test of HL with DHPS protein from E. coli helps in understanding the drug metabolism and has explained the drug–molecule interaction.